Gestión de abastecimiento en la tienda tuti n.032 de la ciudad de Babahoyo. - Cabrera Gómez, Karlenys Damary (2022)
The present investigation called: Supply management in the TuTi Store N.032 of the city of Babahoyo, a chain dedicated to the commercialization and sale of essential goods within the province, has the purpose of determining the problems and anomalies that it presents in local in relation to the shortage of products of greater consumption on the hangers of the warehouse, a factor that greatly reduces customer satisfaction, recognition and preference of the entity, a situation that harms the organization due to the changing and competitive nature of the market. babaho market. The current case applies a descriptive-bibliographical research methodology, which allows describing each of the particular scenarios and situations found in the study based on the supply management presented by local N.032 of the city of Babahoyo of the chain TuTi, based on the information found through the main data collection instruments such as the interview and survey applied to the administrator and manager, respectively, through verifiable theoretical sources that allow an in-depth analysis of the problems raised in the institution.